A case report: Lateral medullary syndrome with facial nerve palsy and hemiparesis. (October 2022) - Shrestha, Ramesh; Kharel, Ghanshyam; Acharya, Shraddha; Pandit, Rohit; Limbu, Nitu
Abstract: Lateral medullary syndrome (LMS) is the most common and severe neurological syndrome associated with atherothrombotic occlusion of the intracranial vertebral artery, followed by posterior inferior cerebellar artery and medullary artery occlusion. It presents as a typical triad of oculosympathetic palsy (Horner's syndrome), ipsilateral gait ataxia, and hypoalgesia with ipsilateral thermoanesthesia of the face. In LMS, the upper motor neuron facial palsy is caused by the involvement of aberrant supranuclear fibers of the facial nerve. The caudal extension of the infarction to the pyramidal tracts may explain contralateral hemiparesis. Here, we have discussed a 42-year-old non-diabetic, hypertensive male with LMS, hemiparesis, and left UMN-type facial palsy. We reported this case because developing nations, have few tertiary level health facilities for neurological examination, and non-neurologists often miss the diagnosis; therefore, the characteristics must be known and understood. Highlights: The patient had hemiparesis, left UMN-type facial palsy, and Horner's syndrome. Dejerine's aberrant pyramidal tract could be the cause of UMN-Facial Nerve palsy. Caudal extension of lesion to pyramidal tracts explains contralateral hemiparesis.